Mannose 6-Phosphate Receptor and Sortilin Mediated Endocytosis of α-Galactosidase A in Kidney Endothelial Cells - Prabakaran, Thaneas (Public Library of Science, 2012)
Prominent vasculopathy in Fabry disease patients is caused by excessive intracellular accumulation of globotriaosylceramide (GL-3) throughout the vascular endothelial cells causing progressive cerebrovascular, cardiac and renal impairments. The vascular lesions lead to myocardial ischemia, atherogenesis, stroke, aneurysm, thrombosis, and nephropathy. Hence, injury to the endothelial cells in the kidney is a key mechanism in human glomerular disease and endothelial cell repair is an important therapeutic target. We investigated the mechanism of uptake of α-galactosidase A (α-Gal A) in renal endothelial cells, in order to clarify if the recombinant enzyme is targeted to the lysosomes via the universal mannose 6-phosphate receptor (M6PR) and possibly other receptors. Immunohistochemical localization of infused recombinant α-Gal A in a renal biopsy from a classic Fabry disease patient showed that recombinant protein localize in the endothelial cells of the kidney. Affinity purification studies using α-Gal A resins identified M6PR and sortilin as α-Gal A receptors in cultured glomerular endothelial cells. Immunohistochemical analyses of normal human kidney with anti-sortilin and anti-M6PR showed that sortilin and M6PR were expressed in the endothelium of smaller and larger vessels. Uptake studies in cultured glomerular endothelial cells of α-Gal A labeled with fluorescence and (125)I showed by inhibition with RAP and M6P that sortilin and M6PR mediated uptake of α-Gal A. Biacore studies revealed that α-Gal A binds to human M6PR with very high affinity, but M6PR also binds to sortilin in a way that prevents α-Gal A binding to sortilin. Taken together, our data provide evidence that sortilin is a new α-Gal A receptor expressed in renal endothelial cells and that this receptor together with the M6PR is able to internalize circulating α-Gal A during enzyme replacement therapy in patients with Fabry disease.